Ambulatory pediatricians: how to bridge the gaps in diagnosis and care coordination for neurodevelopmental disorders in France - Willig, Thiébaut-Noël; Blanc, Jean-Paul; Assathiany, Rémy; Bilbault, Claire; Raffier, Laurent; Werner, Andreas (Frontiers in Pediatrics, 2024)
Introduction and aims The organization of healthcare pathways for neurodevelopmental disorders (NDD) relies on different levels of expertise depending on the complexity of these disorders. NDDs affect between 8% and 15% of children. Historically, national recommendations and healthcare planning measures were initially devoted to autism spectrum disorders and were gradually extended to Attention deficit hyperactivity disorder (ADHD) and specific learning and development disorders. Private doctors play an increasing role in these pathways at different levels of care due to difficulties in organization, particularly in the health and social sector. The aim of this work was to evaluate the contribution of second-line private doctors in the diagnosis and care of children affected by NDD. Methods A first series of surveys in 2016 evaluated the level of commitment of primary care pediatricians; this online national survey was repeated in 2023 among 1,430 members of the French Association of Ambulatory Pediatrics (Association Française de Pédiatrie Ambulatoire: AFPA) to assess their training, current and future involvement, and activity in NDD care. Analysis was performed by the main author using Epi-Info software. Results The study identified in 2023 214 second-line private doctors (14% of all pediatricians in activity), of which 185 agreed to appear in a directory published the same year by the AFPA to facilitate referrals from other professionals. Sex ratio of responders is usual for paediatricians: 79.5%/20.5% (F/M), with a distribution among ages showing a slight increase of the age range between age 51–60 (30.5%). Our data indicate that in France in 2022, second-line private doctors made 48%–53% of NDD diagnoses, 24%–26.4% of follow-up consultations and declare to be accountable for 21% of initial prescriptions for Methylphenidate. Among these second-line doctors, 40% had completed a post-university degree on NDD, 74.3% had completed professional development training (PDT) and 85.2% had completed either or both types of training. Most doctors participating in the survey wanted to improve their level of practice, suggesting that in five years, the number of second-line private doctors will increase by 20% to 244 despite 24 planned retirements within the same period. This data probably underestimates the role of private doctors in NDD diagnosis, follow-up, and initial Methylphenidate prescriptions given the unfavourable working conditions (no financial compensation for long appointments, difficulty accessing paramedical and psychological assessments). Conclusions Our data confirms that diagnosis and care coordination in the various presentations of NDD may rely on different types of practices and specializations: medical and social professionals, mental health professionals, but also a growing body of medical doctors involved in developmental and behavioural pediatrics. This data and reflection will be helpful for organizing healthcare in France or in other countries. Main study limitation relies in the self-declaration of MD's involvement in NDD and could not evaluate the activity of employed MD's from the social and medico social sector, nor be based on the national databases for prescription. It remains however the first attempt of characterization of medical activity at the national level in France for NDD.